The Role of Semaphorin 6D (Sema6D) in Non-Muscle-Invasive Bladder Cancer—A Preliminary Study on Human Plasma and Urine - Piotr Purpurowicz; Tomasz W. Kaminski; Władysław Kordan; Anna J. Korzekwa; Zbigniew Purpurowicz; Zbigniew Jabłonowski (Biomedicines, 2024)
The incidence of bladder cancer worldwide in the last three decades has been increasing in both men and women. So far, there is no established non-invasive bladder cancer biomarker in daily clinical practice. Semaphorin 6D (sema6D) is a transmembrane protein that belongs to the class VI semaphorins. The aim of this study was to evaluate for the first time the potential role of sema6D in bladder cancer. The study group consisted of 40 patients with non-muscle-invasive bladder cancer (NMIBC) and the control group of 20 patients without malignancies. There was a statistically significantly higher urinary sema6D concentration in patients than controls (p < 0.05) but no significant difference in plasma 6D. There were no statistically significant differences in urinary or plasma concentration of sema6D between low- or high-grade cancer and according to the tumor stage in TNM classification. There was a statistically significant negative correlation between plasma sema6D and age of patients (R = −0.6; p = 0.019). Plasma sema6D does not seem to be useful in the clinical practice at this point. However, the urinary sema6D concentration could potentially serve as a marker of NMIBC used for diagnostic purposes, monitoring, and early relapse detection or the assessment of the treatment efficacy. Urinary sema6D is probably not associated with the grading or staging of NMIBC, so it cannot be used for the prediction of disease prognosis.